The Edge as The Choice (A Case Study of Jamu Sellers in Three Traditional Markets, Yogyakarta City) - Arya Putra I Gusti Bagus; Atik Triratnawati (Talenta Publisher, 2021)
The utilization of plants in the health sector has actually been as long as human civilization. This can be seen in jamu as a health care option, which is still in great demand at this time. Over the years, jamu is often identified as a nutritious drink for the lower middle class, but this does not apply to jamu in traditional markets, in Yogyakarta City. The community with various backgrounds also consume jamu. This study aims to find out the reasons behind the choice of Javanese jamu as a health care option in the midst of the modernization of the medical world in Yogyakarta City. This study was conducted in three traditional markets in Yogyakarta City, namely Kranggan Market, Demangan Market, and Prawirotaman Market. This research is a qualitative research with data collection using participatory observation techniques, semi-structured interviews, and literature review. The findings of this research are that jamu, which is considered edge by some, is actually an option for certain parties. Jamu as the center and the edge really depends on the point of view used to see it. The choice of jamu is basically a consumer's self-belief and readiness to change behavior in determining health care choices.